Pengembangan Modul Kimia Berbasis REACT untuk Meningkatkan Keterampilan Berpikir Kritis Siswa Kelas XI IPA SMA/MA - Gazali, Fauzana; Ningsih, Nalia Rahyusri (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2019)
Teaching materials used by teachers in acid-base material have not been able to develop students' critical thinking skills. One solution that can be done to develop students' critical thinking skills is using acid-base module?s based on REACT  (Relating, Experiencing, Applying, Cooperating, and Transferring). The aim of this research is to produce an acid base module based on REACT and reveal its validity and practicality. The type of research used is Research and Development (R&D) using the 4-D model. The module design has been assessed by seven  validators who are Subject Matter Experts (SMEs) consisting of chemistry lecturers from FMIPA UNP and chemistry teachers. While the practicality test was conducted by 3 chemistry teachers and 26 students of class XI MIPA SMAN 1 Padang Panjang. Data analysis techniques in this study used the Content Validity Ratio (CVR) and Cohen's kappa formula. The module design produces three main characteristics, namely: the module is designed in accordance with the prior knowledge of students; the module contains the REACT syntax component; and the module contains aspects of critical thinking skills developed by Ennis. The results of the content validity obtained value of the Content Validity Index (CVI) of 0.90 with a valid category and the results of the construct validity obtained kappa moment of 0.92 with a very high validity category. While the module practicality results according to the teacher and students obtained a kappa moment of 0.86 with a very high practicality category. The conclusion from this study is that the module developed is valid and practical.